Miradessus gen. nov. from South America described for two species previously in Amarodytes Régimbart, 1900 and two new species (Arthropoda, Insecta, Coleoptera, Adephaga, Dytiscidae, Hydroporinae, Bidessini) - Miller, K. B. (2023)
Miradessus gen. nov. is described for two previously described species, Amarodytes pulchellus Guignot, 1955 from Colombia, with new records from Venezuela, and A. plaumanni Gschwendtner, 1935, from Brazil, and two previously unknown species, Miradessus beni sp. nov., from Bolivia and Peru, and Miradessus rikae sp. nov. from Ecuador. The genus is characterized by 1) occipital line absent; 2) basal pronotal striae present; 3) basal elytral stria absent; 4) sutural elytral stria absent; 5) transverse carina on elytral epipleuron at humeral angle absent; 6) distinct marginal bead on anterior clypeal margin absent; and 7) male median lobe deeply multilobed with a dorsal portion separate from a unilobed or bilobed ventral portion.